Landscape tools to support the educational use of school grounds - Jákli, Eszter (Acta Agraria Debreceniensis, 2023)
Recent years have seen an increasing emphasis on child-friendly concepts in landscape architecture and urban planning, as well as a growing emphasis on school grounds and environmental education, both in terms of pedagogy and landscape design. School grounds provide places for active engagement with the environment, for experiencing what is taught in class, and, are therefore of particular importance for education and for building children’s connection with nature. The aim of this research is to develop a set of landscape architecture tools that can be used to promote child-friendly and education-centered design of school grounds. The research collects and organises the different school ground features, drawing on literature research, and the analysis of the Framework Curriculum. The toolkit presented in this paper lists and evaluates each feature according to its function, its relevance to school subjects and the specific knowledge or skills it can help to acquire, its space requirements and feasibility. To conclude, school grounds offer opportunities for teaching almost any subject and can therefore be linked to educational activities in multiple ways. The results of this research are to be developed into design guidelines in order to be used by designers and teachers alike, to help develop school grounds contributing to the well-being and environmental awareness of new generations.